Capitalist income and hierarchical power: A gradient hypothesis - Blair Fix (Forum on Capital As Power - Toward a New Cosmology of Capitalism, 2018)
This paper offers a new approach to the study of capitalist income. Building on the "capital as power" framework, I propose that capitalists earn their income not from any productive asset, but from the legal right to command a corporate hierarchy. In short, I hypothesize that capitalist income stems from hierarchical power. Based on this thinking, I hypothesize that the capitalist fraction of an individual's income is a gradient function of hierarchical power (which I define as the number of subordinates under one's control). Using data from US CEOs, I find evidence that this is true. Furthermore, a hierarchical model of the United States that generalizes this data accurately reproduces many aspects of the US distribution of capitalist income, including the relation between income size and capitalist income fraction. This evidence suggests that the ownership structure of US society is closely linked to the hierarchical structure of firms. This has important implications for the study of income distribution.
Keywords: D31; D33; B5; 330; capitalist income; hierarchy; power; functional income distribution; personal income distribution; inequality; capital as power